Studi Kesiapan Sekolah Mengimplementasikan Kurikulum Merdeka di Kabupaten Sumba Barat Daya - Suluh, Melkianus; Lede, Yulita Adelfin; Bitu, Yuliana Sesi (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This research aims to find out the knowledge and understanding of teachers and principals about the independent curriculum and to find out the readiness of schools to implement the independent curriculum. This research was conducted in Tambolaka City District and Loura District, Southwest Sumba Regency-East Nusa Tenggara. This study is evaluation survey research with a qualitative descriptive approach. The subjects of this study are 24 high school Physics teachers and junior high school science teachers and 12 school principals. Data collection uses interview instruments and questionnaire instruments. The distribution of the questionnaire was carried out using a google form. The analysis is carried out by reducing data, presenting data, and drawing conclusions. The results of the study show that (1) Teachers and Principals who are the subjects of the study have not understood well the concept and strategy of implementing the independent curriculum, (2) Schools are ready to implement the independent curriculum as a form of support for the government's efforts to improve the quality of education, (3) Teachers and Principals of the research subjects have a positive view of the implementation of the independent curriculum on average